Scientifically debatable: Is creatine worth its weight - Rawson, E. S.; Clarkson, P. M. (Sports Science Exchange, 2003)
The purpose of this article is to summarize the available literature concerning the prevalence of, ergogenic effects of, and adverse events associated with creatine supplementation.